Percutaneous Ciaglia tracheostomy: An alternative technique to conventional tracheostomy in patients on mechanical ventilation - Misa, Ricardo; Weiss, Daniel; Bentancourt, Solveig; Morelli, Raúl (Cirugía del Uruguay, 1997)
An alternative technique is presented far the realization of elective tracheostomy in patients in mechanical ventilation. This technique, described by Ciaglia, consists of the introduction of a conventional tracheotomy tube up to width 9, guided by means of the collocation of dilators of increasing width through a guide placed percutaneously by means of a Seldinger procedure. The indications and contraindications of this procedure are determined and technical steps to be followed are shown.